From Flower Farming to Agritourism: The Conditions of (Dis)entanglements and Material (im)mobility in Bahong, La Trinidad amid COVID-19 - Aquino, Chelsea Denise; Calanog, Jericco; Cawed, Jeydah Mari; Guce, Ma. Angelika; Guazon, Hector (anthropozine: The Official Publication of the University of the Philippines H. Otley Beyer Museum of Anthropology, 2025)
Tracing the inflows and outflows of flowers in Bahong, La Trinidad, Benguet during the COVID-19 pandemic uncovers how the owners of flower farms rely on overlapping and extending networks that have provided livelihood and shaped aspirations in times of crises.